Simulasi Mesin Produksi Pada Industri Atap Berbahan Fibercement Menggunakan Aplikasi Promodel - Suwandi, Suwandi (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2019)
Abstract— The development of the property and construction industry as one of the potential industries in Indonesia has a multiplier effects, one of which is on the supply chain of the material supplier industries. The performance of the material supplier industries has a significant influence on the overall success of the property and construction industry. The performance of the material supplier industries can be evaluated through improving the production area to either produce quality products or make the company more productive. In this research, a simulation study was conducted to analyze the production area at PT. XYZ, a building material supplier which produces roofs and ceilings made from fibercement located in Special Region of Yogyakarta Indonesia. The simulation of production system used Promodel application and comprises of three main stages, which are: (1) system modeling, (2) elements definition of the model in Promodel, and (3) simulation and analysis of the result. The result of this research is the percentage of the workload location (work stations/states single and transportation/states multi) has not been distributed as two workstations, distacker section and cutting section, reached 98.11% of workload and 60% of transportation locations had operating loads more than (>) 90%. However, due to the high-operating load at the production system of PT. XYZ, this caused the majority of entities processed properly in the system reaching more than (>) 60%. The result of this study can be used as both for practical references to improve production system and for academics to provide further research opportunities in more specific topics such as line balancing and the measurement of machinery effectivenesses. Keywords—: property and construction; production system; simulation; Promodel.